(untitled) (Nonconventional Technologies Review, 2023)
The International Conference of Nonconventional Technologies 2023 will be organized by the Technical University of Cluj-Napoca, Lucian Blaga University of Sibiu, Romanian Association for Nonconventional Technologies, Romanian Association for Alternative Technologies Sibiu, in the beautiful city of Bistrița, at the headquarters of the University extension of the Technical University of Cluj-Napoca. The event, now in its 22nd Edition, aims to showcase the most recent developments in the area of nonconventional technologies and their applications, in order to stimulate the exchange of valuable opinions and contributions by academia and industry.